2020
DOI: 10.5755/j01.itc.49.3.25265
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Attack Prevention in Mobile Ad-hoc Network (MANET) using Ant Colony Optimization Technique

Abstract: The Mobile ad-hoc networks are auto configured systems where hubs can travel towards any direction. It doesn’t rely on any other frame to build the framework. Because of its versatility, the black hole is a real security issue to be settled. It occurs once a malignant hub referred to as black hole goes into the framework. Black hole center point exhibits its fake lead among the methodology after all disclosure. Currently, varied strategies are made arrangements for Mobile ad-hoc networks. Regardless, at interi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A solitary dark opening is a single attacker node, but an agreeable dark opening assault has a group of assailant nodes collaborating [9][10][11][12] to corrupt the organization's unwavering quality. Furthermore, the black-hole attack node discards every delivered packet, preventing interaction between the source and the target node.…”
Section: Black-hole Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…A solitary dark opening is a single attacker node, but an agreeable dark opening assault has a group of assailant nodes collaborating [9][10][11][12] to corrupt the organization's unwavering quality. Furthermore, the black-hole attack node discards every delivered packet, preventing interaction between the source and the target node.…”
Section: Black-hole Attackmentioning
confidence: 99%
“…Regarding savvy dark opening assault, we imply that the aggressor node knows the pre-owned method, and it can utilize the entirety of its highlights against the other MANET nodes. Khan et al [10] discuss using the Ant Colony Optimization (ACO) Method and Repetitive Routing Setup utilizing Reactive Routing in MANETs to prevent Black Hole Attacks. The above analysis revealed that employing ACO alongside Reactive Routing Protocol resulted in increased effective performance and improved protection of Black Hole Attacks, with a 10% increase overall performance and a 27% reduction in network congestion over Minimal Cost Route System.…”
Section: Related Workmentioning
confidence: 99%
“…The challenging part of communication among MN is to select the most appropriate next node dynamically among a given set of Neighborhood Nodes (NN) in MANET. In MANETs, autoreconfiguration of ad hoc links takes place as and when required by just finding the reachable and nearest MN to route data from Source Node (SN) to Destination Node (DN) [5][6][7][8][9][10]. This, however, does not Hence, there is a need to consider other link and MN metrics to enhance the routing performance [4].…”
Section: Introductionmentioning
confidence: 99%
“…A node can join a single group or multiple groups simultaneously. In MANETs [5][6][7][8][9][10][11][12][13], communication within the network uses nodes, which can be mobile devices, PDAs, tablets, laptops, etc., with Bluetooth, infrared, and Wi-Fi technologies. MANETs can distribute snapshots, audios and videos through its communication technology.…”
Section: Introductionmentioning
confidence: 99%